Effectiveness of 0.01% atropine in anisomyopic children - Azfira Hussain; Aparna Gopalakrishnan; Saurav Chowdhury; Sumita Agarkar (Indian Journal of Ophthalmology, 2023)
Purpose: To investigate the change in ocular parameters of anisomyopic children treated with 0.01% atropine. Methods: This retrospective study analyzed the data of anisomyopic children who underwent comprehensive examination at a tertiary eye center in India. Anisomyopic subjects (difference of ≥1.00 D) of age 6–12 years who were treated with 0.01% atropine or prescribed regular single vision spectacle and had follow-ups of more than 1 year were included. Results: Data from 52 subjects were included. No difference was observed in the mean rate of change of spherical equivalent (SE) of more myopic eyes between 0.01% atropine (−0.56 D; 95% confidence interval [CI]: −0.82, −0.30) and single vision lens wearers (−0.59 D; 95% CI: −0.80, −0.37; P = 0.88). Similarly, insignificant change in the mean SE of less myopic eyes was noted between the groups (0.01% atropine group, −0.62 D; 95% CI: −0.88, −0.36 vs. single vision spectacle wearer group, −0.76 D; 95% CI: −1.00, −0.52; P = 0.43). None of the ocular biometric parameters showed any difference between the two groups. Though anisomyopic cohort treated with 0.01% atropine revealed a significant correlation between the rate of change of mean SE and axial length in both eyes (more myopic eyes, r = −0.58; P = 0.001 and less myopic eyes, r = −0.82; P < 0.001) compared to single vision spectacle wearer group, the change was not significant. Conclusion: Administration of 0.01% atropine had minimal effect on reducing the rate of myopia progression in anisomyopic eyes.